Oil-in-water emulsion formulation of cumin/carvi essential oils combination with enhanced antioxidant and antibacterial potentials. Issue 6 (1st November 2020) - Yakoubi, Sana; Bourgou, Soumaya; Mahfoudhi, Nesrine; Hammami, Majdi; Khammassi, Saber; Horchani-Naifer, Karima; Msaada, Kamel; Tounsi, Moufida Saidani
ABSTRACT: This study targets to explore the bioactivties of the essential oils (EOs) of Cuminum cyminum  and  Carum carvi  alone and three combinations and the impact of the emulsification process on their bioactivities. The mixture of EOs exhibited high reducing power and antiradical activity as well as antibacterial activity. Combination at a ratio of 0.7: 0.3 (cumin-EO: carvi-EO) is effective, ameliorating the antioxidant (reducing power of EC50  value of 11 mg/ml and radical scavenging activity with IC50  value of 24 mg/ml) antibacterial power of the EOs (IZ of 42 and 47 mm against S. aureus and E. faecalis). The lowest droplet size and the highest stability of emulsion have an impact of 1.19 µm with enhanced antioxidant activity (reducing power of EC50  value of 12 mg/ml and radical scavenging activity with IC50  value of 22 mg/ml). This study demonstrated that the combination and emulsification have positive effect on the EOs activity.